Pengaruh Konten Sosial Media TikTok Terhadap Pemahaman Brand Knowledge VOffice Indonesia - Barelvi, Faqih; Menati Fajar Rizki; Mentari Anugrah Imsa (Da'watuna: Journal of Communication and Islamic Broadcasting, 2024)
Brand knowledge plays a very important role in supporting a company's digital marketing efforts by building a positive image, increasing awareness, expanding online presence, building relationships with influential parties, managing crises, and increasing user engagement. vOffice is a virtual office space service provider in various locations in Indonesia. vOffice provides business solutions that include virtual office space rental, physical office space rental, and various other business support services, such as the availability of shared office services, there are various types of products to support the continuity of business activities such as office services, Event Space, Meeting Rooms, Legality Management services to virtual offices. This study aims to obtain information about the effect of tiktok social media content on understanding the brand knowledge of the Voffice Indonesia virtual office through tiktok social media. In this study, the theory used is the S-O-R theory (Stimulus- Organism-Response). S-O-R theory explains the process of how a stimulus produces a response. The most basic interaction occurs when individuals perform actions and receive responses from others The research method used is a quantitative approach with a survey method. This method comes from positivism, which emphasizes empirical experience instead of assumptions or logic. Based on his research objectives to be achieved, he found that the understanding of vOffice brand knowledge through TikTok social media has an influence of 86.6%. It can be concluded that the results of this study show that H0 is rejected and there is an effect of using the TikTok application has great potential as a marketing tool, especially in increasing purchase interest, brand awareness, and brand knowledge of consumers.